Diagnostic Criteria for Obesity Disease in Cats - Okada, Yuki; Ueno, Hiromichi; Mizorogi, Takayuki; Ohara, Kenji; Kawasumi, Koh; Arai, Toshiro (Frontiers in Veterinary Science, 2019)
Accumulated visceral and subcutaneous fat masses were measured with computed tomography (CT) in cats with various body condition scores (BCS) from 5/9 to 9/9. BCS does not always reflect visceral fat accumulation which induces pro-inflammatory reactions. Obese cats with accumulated visceral fat showed low plasma adiponectin and high serum amyloid A (SAA) concentrations, an inflammatory marker. Based on the above results, new diagnostic criteria for obesity disease were established as follows. For overweight cats with high BCS of >7/9, showing 2 or more of the following 3 symptoms, low adiponectin concentrations, hyperlipidemia and high SAA concentrations, categorizes them as having obesity disease. Cats with BCS 6/9 to 9/9, without inflammatory reactions, were classified as simple obesity, which is similar to metabolically healthy obesity (MHO) defined in human medicine. Simple obesity group showed significantly higher adiponectin concentrations than those in control group. The obesity disease group showed significantly higher plasma triglyceride (TG) and SAA concentrations and lower concentrations of adiponectin than the control group. Moreover, plasma glucose and malondialdehyde (MDA) concentrations in the obesity disease group were higher than those in healthy control group, although the differences were not statistically significant. Establishing criteria for obesity disease based on visceral fat accumulation and inflammation markers levels contributes to early and correct diagnosis of obesity in cats.